A new synthesis of public administration : serving in the 21st century - Bourgon, Jocelyne (2011)
*** Part One - Exploring the new frontiers of public administration . 1 - Public administration: not entirely if the past and not yet of the future . 2 - What is different about serving in the 21st century? . 3 - A new synthesis of public administration . 4 - Preparing governments for the challenges of the 21st century . 5 - Government fit for the future . 6 - The new synthesis journey continues *** Part two - Case studies: bridging theory and practice . 7 - The changing reality of practice . 8 - The story of the Singapore prison service: from custodians of prisoners to captains of life . 9 - Bolsa família program: funding families for development . 10 - Vision, collaboration, persistence and hard work: the Canadian federal government's homelessness partnering strategy . 11 - Public safety centres in the Netherlands . 12 - Victorian bushfire reconstruction and recovery authority: a case study on agility and resilience . 13 - Workfare in Singapore . 14 - Citizen-centred public services: designing for complex outcomes *** Part Three - The new synthesis journey . 15 - The new synthesis journey . 16 - The Netherlands roundtable . 17 - The Canada roundtable . 18 - The Brazil roundtable . 19 - The Singapore roundtable . 20 - The United kingdom roundtable . 21 - Group discussions in Australia and new Zealand * Appendix A: Names and affiliations of invited speakers and participants at NS6 international roundtables